Dissecting the Hippocampal Regulation of Approach‐Avoidance Conflict: Integrative Perspectives From Optogenetics, Stress Response, and Epigenetics - Forastieri, C.; Romito, E.; Paplekaj, A.; Battaglioli, E.; Rusconi, F. (Hippocampus, 2024)
ABSTRACT Psychiatric disorders are multifactorial conditions without clear biomarkers, influenced by genetic, environmental, and developmental factors. Understanding these disorders requires identifying specific endophenotypes that help break down their complexity. Here, we undertake an in‐depth analysis of one such endophenotype, namely imbalanced approach‐avoidance conflict (AAC), reviewing its significant dependency on the hippocampus. Imbalanced AAC is a transdiagnostic endophenotype, being a feature of many psychiatric conditions in humans. However, it is predominantly examined in preclinical research through paradigms that subject rodents to conflict‐laden scenarios. This review offers an original perspective by discussing the AAC through three distinct lights: optogenetic modulation of the AAC, which updates our understanding of the hippocampal contribution to behavioral inhibition; the impact of environmental stress, which exacerbates conflict and strengthens the stress‐psychopathology axis; and inherent epigenetic aspects, which uncover crucial molecular underpinnings of environmental (mal) adaptation. By integrating these perspectives, in this review we aim to underline a cross‐species causal nexus between heightened hippocampal activity and avoidance behavior. In addition, we suggest a rationale to explore epigenetic pharmacology as a potential strategy to tackle AAC‐related psychopathology. This review assumes greater significance when viewed through the lens of advancing AAC‐centric diagnostics in human subjects. Unlike traditional questionnaires, which struggle to accurately measure individual differences in AAC‐related dimensions, new approaches using virtual reality and computer games show promise in better focusing the magnitude of AAC contribution to psychopathology.